School Principal’s Strategy Management In Improving The Quality Of Education In Kota Waringin Timur - M. Lamri; Ahmad Mulhakim; Nanang Badrud Tamam (The Faculty of Education and Teaching Training, 2023)
The leadership of the school principal in an effort to improve the quality of education is closely related to the strategy he carries out, so that the principal's strategy is a determinant of whether or not the quality of a school institution is good. The purpose of this study was to determine strategic planning, strategy implementation, and evaluation of school principal strategies in improving the quality of education at MTs Negeri 1 Kotawaringin Timur. The research method is qualitative with a case study approach, collecting data by observation, documentation, and interviews. The results of the research are: (1) Planning for school principals is guided by regulations and refers to the Vision and Mission and goals of the school, conducting an analysis before formulating the program. The strategy set is: a). Teacher Competency Improvement, b). Development and Maintenance of Facilities and Infrastructure, c). Budget Management Efficiency and Effectiveness, d). Discipline and Development of outstanding students, e). Activity Publication. (2) Implementation of the program that has been selected, namely through the process of analysis, communication and coordination with all fields. In implementation, the principal supervises directly the implementation of the program, with the aim of being able to directly address the obstacles found. (3) Evaluation and supervision is carried out directly by supervising the areas of each program. Through a quality assurance agency, the school principal can carry out an evaluation based on the report data for each program implementation. Kepemimpinan kepala sekolah dalam upaya meningkatkan mutu pendidikan erat kaitannya dengan strategi yang dilakukannya, sehingga strategi kepala sekolah merupakan penentu dari baik atau tidaknya mutu dalam suatu lembaga sekolah. Tujuan penelitian ini adalah untuk mengetahui perencanaan strategi, implementasi stretegi, dan evaluasi strategi kepala sekolah dalam peningkatan mutu pendidikan di MTs Negeri 1 Kotawaringin Timur. Metode penelitian yaitu kualitatif dengan pendekatan studi kasus, pengumpulan data dengan observasi, dokumentasi, dan wawancara. Hasil penelitian yaitu: (1) Perencanaan kepala sekolah berpedoman pada regulasi dan mengacu pada Visi dan Misi serta tujuan sekolah, melakukan analisis sebelum perumusan program. Strategi yang ditetapkan yaitu: a). Peningkatan Kompetensi guru, b). Pengembangan dan Pemeliharaan Sarana dan Prasarana, c). Efisiensi dan Efektivitas Pengelolaan anggaran, d). Pendisiplinan dan Pembinaan Siswa berprestasi, e). Publikasi Kegiatan. (2) Implementasi program yang telah dipilih yaitu melalui proses analisis, komunikasi dan berkoordinasi dengan semua bidang. Dalam pelaksanaan, kepala sekolah mengawasi secara langsung terhadap pelaksanaan program, dengan tujuan agar dapat mengatasi secara langsung terhadap kendala yang ditemukan. (3) Evaluasi dan pengawasan dilakukan secara langsung dengan cara melakukan supervisi perbidang setiap program. Melalui lembaga penjamin mutu kepala sekolah dapat melakukan evaluasi yang berpedoman pada data laporan setiap pelaksanaan program.